(untitled) (Palíndromo, 2021)
Giandomenico Tiepolo (1727-1804) made a series of frescoes between 1759 and 1797 in his country residence, Villa Tiepolo, in Zianigo. Transferred to Ca’Rezzonico, in Venice, these paintings provide the contemporary visitor with an intriguing ensemble, in which one can see examples of the artist’s genre painting production, and his work as an observer of contemporary life and social types, but also his imaginative dimension, especially in the Pulcinella room. This article focuses on some of these frescoes, relating them to other works and artists from 18th century Venice, and also placing them in dialogue with researchers at the Commedia dell’Arte, and also with reports of JW Goethe’s trip to Italy and the Divertimento per li regazzi, by Giorgio Agamben. Finally, we explore the works studied as subject to think about the motivations for research in art history, translated into the Warburguian challenge of “seek our ignorance and chase it away”. What Tiepolo did not allow us to see, the mysterious and inapprehensible figure of the Pulcinella makes us think of making art history as a permanent swing whose initial impulse is always not knowing.